2018
DOI: 10.9758/cpn.2018.16.3.253
|View full text |Cite
|
Sign up to set email alerts
|

Different Endocrine Effects of an Evening Dose of Amitriptyline, Escitalopram, and Placebo in Healthy Participants

Abstract: ObjectiveThe primary aim of this study was to further characterize the acute effects of amitriptyline (AMI) and escitalopram (ESC) on serum levels of ghrelin, leptin, cortisol and prolactin in healthy humans.MethodsEleven healthy male participants received a single dose of AMI 75 mg, ESC 10 mg, or placebo (PLA) at 9:00 PM in a double blind, randomized, controlled, repeated measures study separated by one week. Fasting morning serum levels (7:00 AM) of ghrelin, leptin, cortisol and prolactin were assessed.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Furthermore, some studies have found that SSRIs modulate hypothalamic pituitary adrenal (HPA) axis activity. Research has identified both positive and negative changes in plasma and salivary adrenocorticotropic hormone (ACTH) and cortisol following treatment with different SSRIs (Glintborg et al, 2018; Nikisch et al, 2005) – although this is not always observed (Frase et al, 2018). Cortisol modulation of the immune system may also facilitate a host-mediated effect of SSRIs on the GM (Powell et al, 2017).…”
Section: Potential Framework For Ssris Modulation Of the Gut Microbimentioning
confidence: 99%
“…Furthermore, some studies have found that SSRIs modulate hypothalamic pituitary adrenal (HPA) axis activity. Research has identified both positive and negative changes in plasma and salivary adrenocorticotropic hormone (ACTH) and cortisol following treatment with different SSRIs (Glintborg et al, 2018; Nikisch et al, 2005) – although this is not always observed (Frase et al, 2018). Cortisol modulation of the immune system may also facilitate a host-mediated effect of SSRIs on the GM (Powell et al, 2017).…”
Section: Potential Framework For Ssris Modulation Of the Gut Microbimentioning
confidence: 99%
“…Another study [15] indicated that Amitriptyline reduces Ghrelin and Cortisol. Ghrelin lead to food intake [16], and high levels of cortisol are associated with weight increase, especially abdominal obesity [17].…”
Section: Discussionmentioning
confidence: 99%
“…First, we did not control the dosage, types, and duration of medications. Given the possible effects of medication on morning cortisol levels [ 36 , 37 ] future research should adjust the related factors. Second, PTSD patients recruited in this study were not strictly homogeneous in terms of their trauma types (e.g., the patient group included victims of traffic accidents, defectors, etc.).…”
Section: Discussionmentioning
confidence: 99%